2012
DOI: 10.1089/omi.2012.0004
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Expression Data for Identification of Genes Involved in Spatial Accumulation of Calcium in Developing Seeds of Rice

Abstract: The calcium (Ca 2+ ) transporters, like Ca 2+ channels, Ca 2+ ATPases, and Ca 2+ exchangers, are instrumental for signaling and transport. However, the mechanism by which they orchestrate the accumulation of Ca 2+ in grain filling has not yet been investigated. Hence the present study was designed to identify the potential calcium transporter genes that may be responsible for the spatial accumulation of calcium during grain filling. In silico expression analyses were performed to identify Ca 2+ transporters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The majority of TaCAX genes were highly expressed in grain except TaCAX3 group genes, which were highly expressed in root and stem (Figure 6A). The high expression of CAX genes is also reported in seed of rice and Arabidopsis (Goel et al, 2012; Bickerton and Pittman, 2015). …”
Section: Resultsmentioning
confidence: 74%
“…The majority of TaCAX genes were highly expressed in grain except TaCAX3 group genes, which were highly expressed in root and stem (Figure 6A). The high expression of CAX genes is also reported in seed of rice and Arabidopsis (Goel et al, 2012; Bickerton and Pittman, 2015). …”
Section: Resultsmentioning
confidence: 74%
“…Our preliminary study based on rice Ca sensor and transporter data suggests that Ca transporters (especially Ca Exchanger) are the main Ca transporting proteins that pump Ca inside seed. Based on the structural and expression analysis of the calcium transporter genes and available data in literature, a hypothetical model for accumulation of calcium in the cereal grains was proposed (Goel et al, 2011, 2012). The nine calcium transporter genes identified through the analysis of rice MPSS and microarray data were tested and one calcium ATPase and one calcium exchanger was found to be highly expressed in high seed calcium finger millet genotype.…”
Section: Molecular Players Involved In Calcium Transportmentioning
confidence: 99%
“…S1 (booting), S2 (spike emergence), S3 (pollination), S4 (Grain filling or milky) and S5 (seed maturation). (Adapted from Goel et al, 2012). …”
Section: Molecular Players Involved In Calcium Transportmentioning
confidence: 99%
“…Likewise, in silico expression analyses has revealed that CAX genes are highly expressed in the initial stages of seed development in rice (Goel et al . 2012). This suggests that enhanced expression of CAX genes may improve rice varieties (Kim et al .…”
Section: The Cax Transporters In Biotechnologymentioning
confidence: 99%